Hospital admissions for acute myocardial infarction before and after lockdown according to regional prevalence of COVID-19 and patient profile in France: a registry study. (October 2020) - Mesnier, Jules; Cottin, Yves; Coste, Pierre; Ferrari, Emile; Schiele, François; Lemesle, Gilles; Thuaire, Christophe; Angoulvant, Denis; Cayla, Guillaume; Bouleti, Claire; Gallet de Saint Aurin, Romain; Goube, Pascal; et al.
Summary: Background: The COVID-19 pandemic has had a profound effect on general health care. We aimed to evaluate the effect of a nationwide lockdown in France on admissions to hospital for acute myocardial infarction, by patient characteristics and regional prevalence of the pandemic. Methods: In this registry study, we collected data from 21 centres participating in the ongoing French Cohort of Myocardial Infarction Evaluation (FRENCHIE) registry, which collects data from all patients admitted for ST segment elevation myocardial infarction (STEMI) or non-ST segment elevation myocardial infarction (NSTEMI) within 48 h of symptom onset. We analysed weekly hospital admissions over 8 weeks: the 4 weeks preceding the institution of the lockdown and the 4 weeks following lockdown. The primary outcome was the change in the number of hospital admissions for all types of acute myocardial infarction, NSTEMI, and STEMI between the 4 weeks before lockdown and the 4 weeks after lockdown. Comparisons between categorical variables were made using χ 2 tests or Fisher's exact tests. Comparisons of continuous variables were made using Student's t tests or Mann-Whitney tests. Poisson regression was used to determine the significance of change in hospital admissions over the two periods, after verifying the absence of overdispersion. Age category, region, and type of acute myocardial infarction (STEMI or NSTEMI) were used as covariables. The FRENCHIE cohort is registered with ClinicalTrials.gov, NCT04050956 . Findings: Between Feb 17 and April 12, 2020, 1167 patients were consecutively admitted within 48 h of acute myocardial infarction (583 with STEMI, 584 with NSTEMI) and were included in the study. Admissions for acute myocardial infarction decreased between the periods before and after lockdown was instituted, from 686 before to 481 after lockdown (30% decrease; incidence rate ratio 0·69 [95% CI 0·51–0·70]). Admissions for STEMI decreased from 331 to 252 (24%; 0·72 [0·62–0·85]), and admissions for NSTEMI decreased from 355 to 229 (35%; 0·64 [0·55–0·76]) following institution of the lockdown, with similar trends according to sex, risk factors, and regional prevalence of hospital admissions for COVID-19. Interpretation: A marked decrease in hospital admissions was observed following the lockdown, irrespective of patient characteristics and regional prevalence of COVID-19. Health authorities should be aware of these findings, in order to adapt their message if the COVID-19 pandemic persists or recurs, or in case of future major epidemics. Funding: Recherche Hospitalo-Universitaire en Santé iVasc.